2019
DOI: 10.1016/j.ijid.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Anal Ureaplasma spp. positivity among HIV positive men who have sex with men may be associated with high-risk-type HPV infections

Abstract: Objective: HIV positive individuals, particularly men having sex with men (MSM), are at increased risk of sexually transmitted infections (STIs) at genital and extra-genital sites. Data on anorectal Ureaplasma infections are lacking. The aim of our study was to characterize anal Ureaplasma positivity among a cohort of HIV positive MSM and evaluate possible association with papillomavirus infection at the same site. Methods: Anal swab samples, collected as part of routine screening for Chlamydia trachomatis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…HSV and CMV are known as the most frequent opportunistic infections among HIV-positive people, especially among MSM. It was previously shown by different authors HSV I/II and CMV coinfection in HIV-positive and HIV-negative MSM [26,27]. Our data revealed a lower rate of HSV 1 coinfection in HIV-positive MSM in comparison with those in HIV-negative MSM (HSV1: 1.7% vs. 5%), and CMV was detected only in the HIV-positive group.…”
Section: Discussionsupporting
confidence: 64%
“…HSV and CMV are known as the most frequent opportunistic infections among HIV-positive people, especially among MSM. It was previously shown by different authors HSV I/II and CMV coinfection in HIV-positive and HIV-negative MSM [26,27]. Our data revealed a lower rate of HSV 1 coinfection in HIV-positive MSM in comparison with those in HIV-negative MSM (HSV1: 1.7% vs. 5%), and CMV was detected only in the HIV-positive group.…”
Section: Discussionsupporting
confidence: 64%
“…Given the increasing incidence of HPV-associated OPC [41], the observed Ureaplasma spp. positivity exclusively among OPC patients in our study may be a non-negligible finding, particularly considering the fact that previous studies had found an association between Ureaplasma positivity and anogenital dysplasias [14].…”
Section: Non-hpv Sti and Oropharyngeal Carcinomacontrasting
confidence: 48%
“…Co-factors like smoking and immunosuppression were reported to play a meaningful role in the process of HPV-persistence [3,4]. Studies in the past reported that a co-existence of HPV with sexually transmitted infections (STIs) facilitates the persistence and dysplastic transformations of HPV-associated lesions in the cervix or the anus [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cisgendered MSM receive screening for extragenital STIs (de Voux et al, 2019; Tuddenham et al, 2019). Additionally, the risk among PLWH-MSM for high-risk anal human papillomavirus genotypes are common (Borena et al, 2019) as are human papillomavirus infections in the oropharynx (Nakashima et al, 2014) and gonococcal antimicrobial resistance (Johnson Jones et al, 2019). The implications of missed screening opportunities are significant (Berry et al, 2010; Hoover et al, 2010; Patton et al, 2014).…”
Section: Problem Descriptionmentioning
confidence: 99%